Large-scale production of hierarchical TiO2 nanorod spheres for photocatalytic elimination of contaminants and killing bacteria - Bai, Hongwei (2014)
We report a facile non-hydrothermal method for the large-scale production of hierarchical TiO2 nanorod spheres for the photocatalytic elimination of contaminants and killing bacteria. Crescent Ti/RF spheres were prepared by deliberately adding titanium trichloride (TiCl3) to the reaction of resorcinol (R) and formaldehyde (F) in an open reactor under heating and stirring. The hierarchical TiO2 nanorod spheres were obtained by calcining the crescent Ti/RF spheres in a furnace in air to burn off the RF spheres. This method has many merits, such as large-scale production, good crystallisation of TiO2, and good reproducibility, all of which are difficult to realise by conventional hydrothermal methods. The calcination temperature plays a significant role in influencing the morphology, crystallisation, porosity, Brunauer–Emmett–Teller (BET) specific surface area, and hierarchy of the TiO2 nanorod spheres, thus resulting in different photocatalytic performances under UV light and solar light irradiation. The experimental results have demonstrated that the hierarchical TiO2 nanorod spheres obtained after calcination of the crescent Ti/RF spheres at different temperatures displayed similar photocatalytic activities under irradiation with UV light. We attribute this to a balance of opposing effects of the investigated factors. A higher calcination temperature leads to greater light absorption capability of the TiO2 nanorod spheres, thus resulting in higher photocatalytic antibacterial activity under solar light irradiation. It is also interesting to note that the hierarchical TiO2 nanorod spheres displayed intrinsic antibacterial activity in the absence of light irradiation, apparently because their sharp outward spikes can easily pierce and penetrate the walls of bacteria. In this study, the sharpest hierarchical TiO2 nanorod spheres were obtained after calcination at 500 °C, and these exhibited the highest antibacterial activity without light irradiation. A higher calcination temperature proved detrimental to the sharpness of the TiO2 nanorods, thus reducing their intrinsic antibacterial activity.